Women in the New Order Era (A Study of Family Planning and Population Control Policies from 1968 to 1983) - Anifah (CV. Sekawan Siji, 2024)
This journal conducts research on how women's identity was structured during the New Order period from 1968 to 1983. Initially, the policies created by the PKK and KB aimed to control women's movements in the political sphere. Ultimately, these policies became very important because they were used as a means of controlling the state. As this study shows, state policies did not always focus on the welfare and interests of the people. The legitimacy of power was used as a tool for the interests of the people, but it was also used for personal interests or the interests of certain groups. In addition, the legitimacy of power is used to override the rights of the people by resorting to violence to implement established policies. At that time, Indonesian women were undergoing a period of transition.